Vasculitis due to Candidatus Neoehrlichia mikurensis: A Cohort Study of 40 Swedish Patients. (20th August 2020) - Höper, Linnea; Skoog, Elisabet; Stenson, Martin; Grankvist, Anna; Wass, Linda; Olsen, Björn; Nilsson, Kenneth; Mårtensson, Andreas; Söderlind, Jacob; Sakinis, Augustinas; Wennerås, Christine
Abstract: Background: Candidatus ( Ca .) Neoehrlichia (N.) mikurensis is an emerging tick-borne pathogen of humans that is closely related to Ehrlichia and Anaplasma species. This strict intracellular bacterium escapes detection by routine microbiologic diagnostic methods such as blood culture, leading to considerable under-diagnosis of the infectious disease it causes, neoehrlichiosis. Methods: Here, we describe the vascular and thromboembolic events afflicting a series of 40 patients diagnosed with neoehrlichiosis in Sweden during a 10-year period (2009–2019). Results: The majority of the patients (60%) developed vascular events ranging from repeated thrombophlebitis, deep vein thrombosis, pulmonary embolism, transitory ischemic attacks, to arteritis. Younger age was a risk factor for vascular complications. In contrast, there was no difference in the incidence of vascular events between immunosuppressed and immunocompetent patients. However, there were qualitative differences, such that deep vein thrombosis exclusively afflicted the immunosuppressed patients, whereas arteritis was restricted to the immunocompetent persons. We also present the case histories of two patients who developed vasculitis mimicking polyarteritis nodosa and giant cell arteritis. Both were cured by doxycycline treatment. Conclusions: Ca . N. mikurensis infection should be considered in patients living in tick-endemic areas of Europe and northern Asia who present with atypical vascular and/or thromboembolic events. Early diagnosis and antibiotics targeting this emerging infectious agent can eradicate the infection and prevent the development of new vascular events. Abstract : The tick-transmitted bacterial infection neoehrlichiosis is associated with a high incidence of venous vascular and thromboembolic events in immunosuppressed patients. In contrast, infected immunocompetent patients may develop medium- and large-vessel arteritis mimicking systemic rheumatic diseases.